The Role of Indonesian Environment Movement to Respond the Government Policy Regarding Climate Change Issues - Qodarsasi, Umi (State Islamic Institute of Kudus (IAIN Kudus), 2025)
Based on the report from the Intergovernmental Panel on Climate Change (IPCC) in 2013, over the last century, there has been an acceleration of global warming due to the increase in greenhouse gas (GHG) emissions in the atmosphere. This condition is exacerbated by the exploitation of natural resources. The expansion of capital power massively exploits the environment for profit while ignoring social aspects. This paper aims to identify how environmental movements respond to government policies related to global warming issues. Employing a descriptive qualitative methodology, the research explored the role of Wahana Lingkungan Hidup (WALHI) as an environmental movement in responding to government policies through advocacy, campaigns, research, and education. The study identified that WALHI conducts advocacy in coastal areas and small islands concerning the impacts of climate change and the RZWP3K policy, which threatens environmental sustainability in coastal areas.